Investigation of conventional and ultrasonic vibration-assisted turning of hardened steel using a coated carbide tool - Ghule, Govind S.; Sanap, Sudarshan; Chinchanikar, Satish; Cep, Robert; Kumar, Ajay; Bhave, Suresh Y.; Kumar, Rakesh; Altarazi, Faisal (Frontiers in Mechanical Engineering, 2024)
This study compares conventional turning (CT) and ultrasonic vibration-assisted turning (UVAT) in machining hardened AISI 52100 steel (62 HRC) with a PVD-coated TiAlSiN carbide tool. UVAT experiments, utilizing an ultrasonic frequency of 20 kHz and vibration amplitude of 20 µm, varied the cutting speed, feed, and depth of cut. Remarkably, UVAT reduced tool wear, extending tool longevity. Surprisingly, power consumption showed no significant differences between CT and UVAT. Mathematical models based on experimental data highlight the substantial impact of the cutting speed on tool wear, followed closely by the depth of cut. For power consumption, the depth of cut took precedence, with the cutting speed and feed rate playing pronounced roles in UVAT. This emphasizes the potential for further research on machinability, particularly exploring different vibration directions on the tool in feed, tangential, and radial aspects.